The effectiveness of educational intervention to improve health promoting behavior on prevention of osteoporosis among women: Application of BASNEF model - Shima Moradnejad (حیات, 2020)
Background & Aim: Osteoporosis is a silent and progressive disease that causes disability in people particularly women, with age and has irreversible consequences in their lives. This study aimed to determine the effect of an educational intervention program based on BASNEF model on prevention of osteoporosis among women referred to health centers in the south of Tehran. Methods & Materials: This is a quasi-experimental study with two groups of intervention and control, performed on 162 women (81 in the intervention group and 81 in the control group) aged 30-49 years, referred to health centers in the south of Tehran in 2018. The data collection tool included demographic information, a researcher-made questionnaire based on BASNEF model constructs and another part of the questionnaire was Health Promotion Standards Questionnaire (HPLP II). Questionnaires were completed for both the intervention and control groups before and six months after the intervention. Data were analyzed by the SPSS software using chi-square, t-test, and paired t-test at a significance level of 0.05. Results: The mean of women’s age in this study was 37.79±5.47 years old. There was no significant difference in demographic variables and BASNEF model constructs before the intervention (P>0.05). After the intervention, the mean score of BASNEF model constructs and the dimensions of health promoting behaviors significantly increased in the intervention group (P<0.001). Conclusion: The study results revealed a positive effect of the BASNEF model-based educational program on health promoting behaviors regarding osteoporosis prevention among women. It is suggested to use this model as a successful model in educational interventions to prevent osteoporosis in women. Clinical trial registry: IRCT20130213012460N15